2007
DOI: 10.1002/elps.200600463
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in enhancing the sensitivity of electrophoresis and electrochromatography in capillaries and microchips

Abstract: Poor sensitivity is considered to be one of the major limitations of electrophoretic separation methods, particularly when compared to traditional liquid chromatographic techniques. To address this issue, various in-line preconcentration techniques have been developed over the past 15 years, ranging in power and complexity, and there are now a number of well understood approaches routinely capable of providing a 10,000- to 100,000-fold increase in sensitivity, as well as several that can be pushed above a mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
195
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(200 citation statements)
references
References 287 publications
(219 reference statements)
1
195
0
Order By: Relevance
“…Field amplification also increases mass loading since large volume samples can be preconcentrated on-capillary, thus enhancing sensitivity [8][9][10]. Sample preconcentration and stacking techniques have recently been reviewed by Breadmore [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Field amplification also increases mass loading since large volume samples can be preconcentrated on-capillary, thus enhancing sensitivity [8][9][10]. Sample preconcentration and stacking techniques have recently been reviewed by Breadmore [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a combination of high-performance liquid chromatography and CE where EOF is used instead of a hydraulic pump to move the mobile phase through the capillary [38,39]. Strictly, capillary (electro)-chromatography (CEC) is not a variation on CE but a variation on chromatography since the separation of analytes is not based on differences in the electrophoretic mobility.…”
Section: Capillary (Electro)-chromatographymentioning
confidence: 99%
“…Therefore, various online sample preconcentration techniques have been developed to improve the sensitivity of MCE. [6][7][8][9][10] One of the successful strategies is to combine other preconcentration devices with MCE on a single microchip, e.g., solid-phase extraction, 11 filtering using a nanopore or nanochannel, 12,13 and so on. 14,15 As a typical example, Kim et al reported that the preconcentration with a nanochannel could attain a million-fold improvement of the detectability, but it required a long analysis time of over 30 min.…”
Section: Introductionmentioning
confidence: 99%